Comprehensive study on physicochemical characteristics of magnetorheological elastomer featuring epoxidized natural rubber - Yusoff, M.S. (IOP Publishing Ltd, 2022)
The effect of the epoxidation level of epoxidized natural rubber (ENR) on the physicochemical characteristics of magnetorheological elastomer (MRE) made from it was studied. MRE samples were fabricated by mixing ENR with additives and carbonyl iron particles (CIP), followed by vulcanisation at 150 Â°C for 30 min. The factors that are manipulated for this study include the epoxidation level of ENR, through the use of ENR 25 and ENR 50 as the polymer matrix, and the proportion of the components of the composite, through varying the amount of CIP added in the mixing step. The analysis was performed by measuring the physicochemical characteristics of the MRE, which include curing time, magnetisation, functional group composition, thermal stability, and morphology. The cure time (t 90) of the MRE increased with increasing CIP content while the scorch time (ts2) decreased. Electron microscopy showed that the CIP were randomly distributed throughout the MRE samples, indicating an isotropic MRE. The MRE fabricated with ENR 25 and 70 wt CIP had a considerably higher value of saturation magnetisation at 42.54 emu g-1, whereas the MRE fabricated with ENR 50 and 70 wt CIP had a saturation magnetisation of 40.80 emu g-1. Hydrogen bonds were created between the epoxy bonds in the epoxidized rubber and the hydroxyl groups from the CIP and other additives. Thermogravimetric analysis indicated an improvement in thermal stability, as the addition of CIP delayed the thermal degradation of the MRE. The results showed that the epoxidation level of the natural rubber has a significant effect on the physicochemical characteristics of the MRE fabricated from it. Overall outcomes showed that both ENR 25 and ENR 50 could be used as an alternative matrix material for fabricating an MRE, with the choice falling on the application specification. Â© 2022 IOP Publishing Ltd.